Recent advances in iPSC technology - Birbrair, Alexander (Advances in stem cell biology ;, 2021)
"Somatic cells can be reprogrammed into iPSCs by the expression of specific transcription factors. These cells are transforming biomedical research in the last 15 years. The volume teaches readers about current advances in the field. This book describes different technologies and strategies to use iPSCs for biological and clinical benefit. In recent years, remarkable progress has been made in the obtention of iPSCs and their differentiation into several cell types, tissues, and organs using state-of-the-art techniques. These advantages facilitated identification of key targets and definition of the molecular basis of several disorders. This volume will cover hot topics in the iPSC field, such as iPSCs for modeling the cardiovascular toxicities of anticancer terapies, iPSC differentiation through the lens of the noncoding genome, modeling of blood-brain barrier with iPSCs, mathematical modeling of iPSCs, iPSCs to study human brain evolution, self-renewal in iPSCs, differences and similarities between iPSCs and embryonic stem cells, and more"--Page 4 of cover.